Dendritic nanoconjugates for intracellular delivery of neutral oligonucleotides. Issue 29 (2nd July 2015) - Ming, Xin; Wu, Lin; Carver, Kyle; Yuan, Ahu; Min, Yuanzeng
Abstract : Conjugation of neutral oligonucleotides (ONs) with PAMAM dendrimers resulted in ultra-small nanoconjugates that combine superior ON delivery and reduced cytotoxicity. Abstract : Dendrimer-based gene delivery has been constrained by intrinsic toxicity and suboptimal nanostructure. Conjugation of neutral morpholino oligonucleotides (ONs) with PAMAM dendrimers resulted in neutral, uniform, and ultra-small (∼10 nm) nanoconjugates. The nanoconjugates dramatically enhanced cellular delivery of the ONs in cancer cells. After release from the dendrimer in the cytosol, the ONs produced potent functional activity without causing significant cytotoxicity. When carrying an apoptosis-promoting ON, the nanoconjugates produced cancer cell killing directly. Thus, the dendritic nanoconjugates may provide an effective tool for delivering ONs to tumors and other diseased tissues.